IMPLEMENTASI PROGRAM KKNT DALAM PEMBERDAYAAN MASYARAKAT DI DESA BUNGA KARANG - Al Kautsar, Muhammad Kevin; Handayani, Agustin Tri; Agus Tria Ahmad Wijaya; Aliya Dewi Sapon Ratu; Az Zahra Ramanda Putri; Dela Septriawati; Putri Amanda Astri; Rizka Yuniarsa; Ahmad Khudri (Education, Language, and Arts: Jurnal Pengabdian Kepada Masyarakat, 2025)
This study aims to describe the implementation of the KKN-T program in empowering the community of Bunga Karang Village, Tanjung Lago District, Banyuasin Regency. A qualitative descriptive method was employed to obtain an in-depth understanding of the program implementation. Data were collected through observation, interviews, and documentation during the KKN-T activities. The results indicate that the KKN-T program had a positive impact on the community, particularly in the fields of education, health, environmental sustainability, and village infrastructure development. Teaching activities in elementary schools increased students’ learning motivation and character development, health socialization programs enhanced community awareness of stunting prevention and balanced nutrition, environmental greening activities improved village aesthetics, and the construction of a village gate strengthened local identity. Overall, the implementation of KKN-T encouraged community participation, contributed to sustainable village development, and provided valuable experiential learning for students. Penelitian ini bertujuan untuk mendeskripsikan implementasi program KKN-T dalam pemberdayaan masyarakat di Desa Bunga Karang, Kecamatan Tanjung Lago, Kabupaten Banyuasin. Metode yang digunakan adalah metode kualitatif dengan pendekatan deskriptif. Pengumpulan data dilakukan melalui observasi, wawancara, dan dokumentasi selama pelaksanaan kegiatan KKN-T. Hasil kegiatan menunjukkan bahwa program KKN-T memberikan dampak positif bagi masyarakat desa, khususnya dalam bidang pendidikan, kesehatan, lingkungan, dan pembangunan fisik desa. Kegiatan mengajar di sekolah dasar meningkatkan motivasi dan karakter siswa, sosialisasi kesehatan meningkatkan pemahaman masyarakat mengenai stunting dan gizi, program penghijauan memperbaiki kualitas lingkungan, serta pembangunan gapura memperkuat identitas desa. Secara keseluruhan, implementasi KKN-T mampu mendorong partisipasi masyarakat dan memberikan manfaat nyata bagi pembangunan desa sekaligus menjadi sarana pembelajaran kontekstual bagi mahasiswa.